Studies on the application of wavelet families for a high impedance fault location algorithm in a distribution network - Ali, M.S.; Bakar, Ab Halim Abu; Tan, Chia Kwang; Mokhlis, Hazlie; Arof, Hamzah (Turkiye Klinikleri Journal of Medical Sciences, 2016)
Detecting high impedance faults in a distribution network is a great challenge and locating one is even more challenging. This paper will present an enhanced high impedance fault location algorithm based on the database technique. This paper is an extension of a faulty section identification algorithm developed previously. However, in this paper, the performance of the previous algorithm is investigated first in terms of different sampling rate and window size. Then these parameters will be used as a standard parameter to study the effectiveness of different types of mother wavelets. Each mother wavelet will be used to extract important features of a voltage signal from a single measurement point in a typical 38-node underground distribution network.